Aging in Place - A mixed methods study protocol of how care providers in Sweden organise and adapt granted home care services to the preferences and needs of people living with dementia - Annika Taghizadeh Larsson; Anna Olaison; Lars-Christer Hydén; Mattias Antar; Ceciel Heijkants; Jimmy Lindberg; Sofia Nordmark; Veronika Wallroth; Susanne Kelfve (PLoS ONE, 2026)
The project Aging in Place applies a novel approach to investigate how social care services in Sweden are adapted to preferences and needs of older persons (65 years and older) living at home with dementia, including their partners. The project covers the process that starts when a person is granted to receive services, which are communicated to a care provider – who should organize the services – and finally reach the receiving older person. This approach differs from previous research on elder care, which has focused either on the purchaser or the provider side of Swedish municipal elder care in the purchaser-provider model Sweden adopted since the mid-1990s. The project focuses on: 1) what specific social care services older persons living at home with dementia are granted; if a dementia diagnosis is needed for some services; and the differences between municipalities; 2) how care providers organise granted services and adapt them to people living with dementia; including differences between municipalities and care provider units; 3) how care recipients living with dementia (including co-habiting partners) experience and influence the receiving of services. The ambition is to generate both generalisable knowledge about social care services for people living with dementia in Sweden, including differences between municipalities and care providers, and in-depth, exploratory knowledge about how care providers organise services and how these services are received by care recipients. The project encompasses a necessary combination of methods and materials: register studies, web surveys, as well as observations and interviews. The project will provide important, elemental, knowledge on Swedish dementia- and eldercare. This knowledge is needed as a basis for further studies and as a contribution to discussions on how future social care can be developed to ensure people living with dementia, and their partners, equality, participation, and dignity in later life.